Dynamics Between Foreign Portfolio Investment, Stock Price and Financial Development in South Africa: A SVAR Approach - Kazeem Abimbola Sanusi; Zandri Dickason-Koekemoer (Economies)
The goal of this study is to look into the dynamic relationship between stock prices, foreign portfolio investment, and financial development in the South African economy. Federal Reserve Economic Data (FRED) provided quarterly time series data from 1960 (Q1) to 2024 (Q2). This study uses a structural VAR estimation approach and dynamic conditional correlation (DCC GARCH model). The DCC GARCH approach displays time-varying correlations between stock prices, credit given to the private sector as a measure of financial growth, and foreign portfolio investments. The dynamic links between stock prices, financial development, and foreign private investment (FPI) are examined using the SVAR technique. Our findings show that a financial development shock encourages and provokes a substantial influx of foreign portfolio investment into the South African economy. This suggests that overseas portfolio investments react favorably and notably well to favorable shocks in the financial development process. We suggest that a stable financial system framework and lower credit costs would strengthen the impact of higher stock prices on private sector credit and guarantee that higher stock prices have a beneficial impact on other financial development metrics. Better financial development metrics, such as credit to the private sector, will therefore increase foreign portfolio investment.